Architectural features of the Ganesha Temple - Temples of India Project Team (Jio Institute, 2024)
The temple features architectural elements such as khura, kumbha (pot-shaped), kalasha (a pitcher), and kapotapalikas (cyma recta moulding), upon which a plain jangha (wall) rises. Above the jangha, a varandika (moulded parapet) is placed which supports the shikhara (superstructure), adorned with bricks marked with chaitya arches.